ADVOKAT SEBAGAI UPAYA BANTUAN HUKUM DALAM PENYELESAIAN PERKARA - Alfarizkie Alqorni; Fakhry Wahyuda Siregar; Prasetyo Seto Putro; Surya Rahman Lubis; Muhammad Rafly (JOURNAL SAINS STUDENT RESEARCH, 2025)
The legal profession in Indonesia plays a crucial role in providing legal aid to the public, particularly in the resolution of cases through regular and extraordinary legal remedies. Regular legal remedies, such as appeals, cassation, and judicial reviews, are conducted in accordance with established procedures to seek justice. Meanwhile, extraordinary remedies include actions like clemency and rehabilitation, which can only be taken under certain conditions and with special considerations. As a noble profession, advocates are responsible for defending their clients' rights both in court and in out-of-court dispute resolution. This research employs a normative legal research method to analyze the role of advocates in providing legal assistance and their contribution to the enforcement of law and justice in Indonesia. Despite the guarantee of equality before the law, obstacles such as high costs and legal ignorance can hinder access to justice. Therefore, advocates play an essential role in ensuring that the public, especially the underprivileged, receive their legal rights during legal proceedings. Through the legal aid they provide, advocates help facilitate the judicial process and promote the achievement of justice for all members of society.